(untitled) (Scientific journal of the Fergana State University, 2023)
The structures of the rule of law and civil society are phenomena of culture. They are not gifted by nature, but created by people consciously and specifically to meet their social needs. Therefore, in this article we have tried to focus on the legitimate processes of state formation. Also, attention is paid to the implementation by the state of regulatory law in legal life, where the legal culture of society, including laws and regulations, serve as legal consciousness and the legal basis of its powers. In general, the cultural whole is considered the basis of the existence and development of society, and on its basis they tried to explain the origin of the four correlative-functional laws of society.